Islamic Economics and Sustainable Development Goals In Jeneponto Regency - Juardi,; Rahman B, Aulia; Iwang, Baso; Nurul Utama, Isra; Kafrawi Mahmud, Ahmad (LAA MAISYIR : Jurnal Ekonomi Islam, 2022)
The purpose of this study is to analyze the achievement of sustainable development goals (SDGs) in Jeneponto Regency as part of the parameters of the progress of Islamic civilization. This research is a quantitative research using path analysis (path analysis). The research results show that PAD has a negative effect on economic growth, but a positive effect on unemployment.  While DAU has a positive effect on economic growth, it has a negative effect on unemployment.  The DAK variable has a negative effect on economic growth and unemployment, both directly and through economic growth.  The implication of the findings of this research is that the formulation of development policies and strategies has not been maximized in this area, so the impact on the achievement of the SDGs is still low.  The implementation of the SDGs in Jeneponto Regency has deviated from the path of Islamic values, as in Islam it is explained that economic development aims to achieve people's welfare and prosperity which is called the Falah concept.  Without justice and fairness to humans and nature, Falah will never be achieved, especially in creating inclusive economic growth.